1983
DOI: 10.2466/pms.1983.57.2.649
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Study of Short-Term Memory Characteristics for Kinesthetic Movement Information

Abstract: The present experiment was designed to examine age-related characteristics of short-term retention of kinesthetic movement information. 20 children from each age group (6, 8, 10 yr.) were tested for recall of kinesthetic end-location. The results indicate that 6- and 8-yr.-old children became less accurate and more variable in recall performance following a delay interval. However, 10-yr.-old children were capable of maintaining performance accuracy during a delay interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…by comparison with other modalities such as touch and visios it was concluded from these experiments that kinaesthetic development occun at a relatively older age. This finding is in agreement with other developmental studies using passive movement tasks which have found greatest at least 7 years of age (Ashby, 1983;Henderson & Duncornbe, 1982). Other studies which have used active movement tasks (movements initiated and guided by the subject) have indicated a slightly earlier acquisition of kinaesthetic sensitivity (Elliott, Comlly, & Doyle, 1988; Hoare & Larkin, 1991;Smothergill.…”
supporting
confidence: 93%
“…by comparison with other modalities such as touch and visios it was concluded from these experiments that kinaesthetic development occun at a relatively older age. This finding is in agreement with other developmental studies using passive movement tasks which have found greatest at least 7 years of age (Ashby, 1983;Henderson & Duncornbe, 1982). Other studies which have used active movement tasks (movements initiated and guided by the subject) have indicated a slightly earlier acquisition of kinaesthetic sensitivity (Elliott, Comlly, & Doyle, 1988; Hoare & Larkin, 1991;Smothergill.…”
supporting
confidence: 93%
“…This method has been repeatedly used in a number of other studies, and is well established (e.g. Townsend & Ashby, 1983). To remove outliers, responses with reaction times more than two SDs from the mean of that particular condition (for that subject) were removed from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous investigation on mental imagery has principally concentrated on adult athletes, fewer studies have examined the young athlete population. Ashby (1983) have showed that imagery ability does not grow completely until 7 years of age. Parker and Lovell (2009) discovered high improvement in imagery ability in athletes between 7 and 17 years of age.…”
Section: Introductionmentioning
confidence: 99%